Dosimetric Comparison of Intraoperative Radiotherapy and SRS for Liver Metastases - Scafa, Davide; Muedder, Thomas; Holz, Jasmin A.; Koch, David; Nour, Younéss; Garbe, Stephan; Gonzalez-Carmona, Maria A.; Feldmann, Georg; Vilz, Tim O.; Köksal, Mümtaz; Giordano, Frank A.; Schmeel, Leonard Christopher; et al. (Frontiers in Oncology, 2021)
Purpose/Objectives: To perform a dosimetric comparison between kilovoltage intraoperative radiotherapy (IORT) and stereotactic radiosurgery (SRS) simulating both deep-inspiration breath-hold (DIBH) and free-breathing (FB) modalities for patients with liver metastases. Methods/Materials: Diagnostic computed-tomographies (CT) of patients who underwent surgery were retrospectively screened and randomly selected for the study. An internal target volume (ITV) margin was expanded 1 cm craniocaudally and 0.5 cm radially from the gross tumor volume (GTV) for FB-SRS. A 0.5 -cm planning target volume (PTV) was created for both DIBH- and FB-SRS plans. Accounting for the maximal GTV diameters, a modified GTV (IORT-GTV) was expanded circumferentially to simulate a resection cavity. The best suitable round-applicator size was thereafter selected. All treatment plans were calculated homogeneously to deliver 40 Gy. Doses delivered to organs at risk (OAR) and target volumes were compared for IORT vs. both SRS modalities. Results: Eight patients encompassing 10 lesions were included in the study. The mean liver volume was 2,050.97 cm3 (SD 650.82) and mean GTV volume 12.23 cm3 (SD 12.62). As for target structures, GTV-IORT (19.44 cm3 [SD 17.26]) were significantly smaller than both PTV DIBH-SRS (30.74 cm3 [SD 24.64], p=0.002) and PTV FB-SRS (75.82 cm3 [SD 45.65], p=0.002). The median applicator size was 3 cm (1.5 – 4.5) and the mean IORT simulated delivery time was 45.45 min (SD 19.88). All constraints were met in all modalities. Liver V9.1 showed significantly smaller volumes with IORT (63.39 cm3 [SD 35.67]) when compared to DIBH-SRS (150.12 cm3 [SD 81.43], p=0.002) or FB-SRS (306.13 cm3 [SD 128.75], p=0.002). No other statistical or dosimetrically relevant difference was observed for stomach, spinal cord or biliary tract. Mean IORT D90 was 85.3% (SD 6.05), whereas D95 for DIBH-SRS and FB-SRS were 99.03% (SD 1.71, p=0.042) and 98.04% (SD 3.46) p=0.036), respectively. Conclusion: Kilovoltage IORT bears the potential as novel add-on treatment for resectable liver metastases, significantly reducing healthy liver exposure to radiation in comparison to SRS. Prospective clinical evidence is required to confirm this hypothesis.